Die funksie van die gemeenskapsverpleegkundige in kuratiewe distriksgesondheidsdienste - H P SMIT; Dr S D Roos (AOSIS, 2000)
In South Africa patients are discharged sooner from hospitals, because of a shortage in hospital beds, thus more patients are nursed at home. More prominence should be given to the function of the community nurse in these mainly curative health services. An explorative and descriptive study was performed in order to explore and describe the functions of the community nurse in the context of the district health service in South Africa. These functions described in this article were determined by means of an analysis of duty sheets as well as the use of questionnaires which was based on a literature study. Some conclusions and recommendations were made on which the community nurse can base these nursing services.